Snowbound with her mountain cowboy - Johns, Patricia (Romance writer) (Harlequin heartwarming, 2021)
"A lost memory... Could mean a second chance! Mountain resort owner Angelina Cunningham has her hands full with a massive winter storm. Which is exactly when her ex-husband arrives, injured and suffering temporary amnesia. Ben King has always been her weakness. Though he doesn't remember her, he's still as charming and sweet as ever, and Angelina is falling form him all over again. But can their rekindled love outlast the storm and the return of their past mistakes?" --page [4] of cover